Rancang Bangun Aplikasi Apotek Pada Apotek Ashara Husada - Atmaja, Nicko Happy; Sunarto, Dewiyani; Ayuningtyas, Ayuningtyas (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2015)
Ashara Husada pharmacy is in cooperation with YAKES health foundation PT .Telkom Indonesia. This health foundation formed to serve needs of health for the employees, retired employees, and their families those residing in Sidoarjo and the surrounding areas. Clinics and pharmacies Ashara Husada not only serve the employees, retired employees, and families, but also conducts services for the public. The difficulty lies in the recording of the transactions are still manual , a period of of purchase the medicines are not periodically and stocks information of medicines being inaccurate. After were analysed the existing problems then it leads to Design of pharmacy. Design help to recording the transactions, handle a shortage and excess stock of medicines, as well as displaying dashboard of the medicines, medicines sales, stock of medicines, and rejection of the sale of medicines. From the trial of the application of the pharmacy can help pharmacists’s work there are 1 ) records the transactions of medicines, 2 ) handle deficiency and excess stock medicines with rop calculation 3 ) displaying dashboard from sales of a medicines, the purchase of medicines, stock of medicines and rejection medicine’s sales.